(untitled) (KULT_online, 2022)
A Regarded Self: Caribbean Womanhood and the Ethics of Disorderly Being by Kaiama L. Glover places five female characters of anglophone and francophone Caribbean literature center stage and defines the specific ways in which these women regard themselves as a practice of freedom and as their forming of an ethics of disorderly being that is necessary for survival. It is a thoughtful consideration of female subjectivity in a (post)colonial world and meaningfully subverts and unsettles ideological perspectives and academic discourses.